2006
DOI: 10.2174/156802606776743075
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MRI and PET/SPECT in Alzheimers Disease

Abstract: Alzheimer's disease (AD) is difficult to diagnose in its early stages, and even if detected early, there is no preventative treatment. Imaging modalities such as MRI, PET, and SPECT have the potential to contribute to both the diagnosis of Alzheimer's disease, as well as assist in the search for more effective treatments. A number of AD-related biomarkers have been proposed and evaluated. The use of PET imaging to detect alterations in regional brain metabolism using [(18)F]FDG has enabled more sensitive and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 154 publications
(261 reference statements)
0
36
0
Order By: Relevance
“…For example, Behar et al [24] believe that the rise in mIns corresponds to the most marked astrocytic reaction and might reflect a specific glial response in hamsters with Creutzfeldt-Jakob disease. Coimbra et al's studies have shown a correlation of increased mIns with AD pathology [25] . In the present study, the results of GFAP staining showed that there were activated and hyperplastic astrocytes in the frontal cortex and hippocampus of 3-month-old AD mice, while no A ␤ plaques were detected and neurons were also not abnormally damaged.…”
Section: Discussionmentioning
confidence: 95%
“…For example, Behar et al [24] believe that the rise in mIns corresponds to the most marked astrocytic reaction and might reflect a specific glial response in hamsters with Creutzfeldt-Jakob disease. Coimbra et al's studies have shown a correlation of increased mIns with AD pathology [25] . In the present study, the results of GFAP staining showed that there were activated and hyperplastic astrocytes in the frontal cortex and hippocampus of 3-month-old AD mice, while no A ␤ plaques were detected and neurons were also not abnormally damaged.…”
Section: Discussionmentioning
confidence: 95%
“…[17][18][19] Atrophy rates have been reported to be larger in entorhinal cortex than in the hippocampus (w7% per year versus w6% per year), 20 but difficulties in unambiguously defining this brain structure on the basis of landmarks make entorhinal cortex measurements highly variable. 21 In general, manual regions-of-interest measurements are both operator-dependent and labor-intensive.…”
Section: Structural Mrimentioning
confidence: 99%
“…21 Diffusion-Weighted Imaging and Diffusion-Tensor Imaging Several studies have used the apparent diffusion coefficient or diffusion characteristics derived from DTI to gain information on demyelinization and axonal loss in the context of Alzheimer's disease. The apparent diffusion coefficient provides information on the overall mobility of tissue water while DTI provides additional directional information on this diffusion process.…”
Section: Structural Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of regional cerebral blood flow (rCBF) using single-photon emission computer tomography (SPECT) or positron-emission tomography (PET) may be applied as supplemental investigations in patients with cognitive symptoms. Results from these methods will typically demonstrate regionally reduced blood flow or glucose metabolism in AD [4] , and several reports have suggested that focally reduced blood flow or metabolism can be present very early in the cause of the disease, which may increase the diagnostic certainty in AD [4][5][6][7][8][9] . Advanced methods for parametric image analysis and statistical parametric mapping have been available for some years.…”
Section: Introductionmentioning
confidence: 99%